2016
DOI: 10.1016/j.polymer.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Length scale dependence in elastomers – comparison of indentation experiments with numerical simulations

Abstract: Probing depth dependent deformation at nano-and micrometer length scales has been observed in indentation experiments of polymers. Unlike in metals, where size effects are observed in plastic deformation and are attributed to geometrically necessary dislocations, the origin of size dependence in polymers is not well understood. As classical continuum theories are unable to describe such phenomena, higher order gradient theories have been developed to capture such size dependent deformation behavior. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Nevertheless, the spherical indenter may be advantageous in cases where limited or no damage at the surface is in need. Furthermore, from the same set of results it is inferred that for decreasing R the effective Young's modulus E ef f increases in accordance with the results of Garg et al (2016).…”
Section: Accepted Manuscriptsupporting
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, the spherical indenter may be advantageous in cases where limited or no damage at the surface is in need. Furthermore, from the same set of results it is inferred that for decreasing R the effective Young's modulus E ef f increases in accordance with the results of Garg et al (2016).…”
Section: Accepted Manuscriptsupporting
confidence: 83%
“…In particular, size effects in polymers have been attributed to surface effects (Zhang and Xu, 2002;Zhang et al, 2004), A C C E P T E D M A N U S C R I P T friction (Lim and Chaudhri, 2006), tip imperfections (Flores and Calleja, 1998), material inhomogeneities (Briscoe et al, 1998), surface adhesion (Johnson et al, 1971), as well as multi-physics phenomena such as piezoelectricity (Giannakopoulos amd Suresh, 1999), magnetoelasticity (Giannakopoulos end Parmaklis, 2007), and flexoelectricity (Mao et al, 2016). It seems, however, that the contact related size phenomenon is mainly the result of the imposed higher order displacement gradients emerging in the vicinity of the tip of the indentor (Briscoe et al, 1998;Chong and Lam, 1999;Alisafaei et al, 2014;Lam and Chong, 1999;Lam and Chong, 2000;Lam and Chong, 2001;Swaddiwudhipong et al, 2005;Nikolov et al, 2007;Han, 2010;Alisafaei et al, 2013;Voyiadjis et al, 2014;Garg et al, 2016). It has been further shown that size effects in elastomers are considerably more pronounced than in thermoset or thermoplastic polymers in which the size effect is attributed to their molecular structure.…”
Section: A N U S C R I P T 1 Introductionmentioning
confidence: 99%
“…Previous reports have shown that a spherical indentation depth [ h ( t )] of less than 15%, as compared to the thickness of an elastoplastic material, results in K ( t ) that is close to the actual value . It has been emphasized that the sphere radius plays a significant role in K ( t ) measurements . The instantaneous strain ratio corresponding to the spherical indentation test is the ratio of h ( t ) to the sample thickness [ H ( t )].…”
Section: Introductionmentioning
confidence: 99%
“…22 It has been emphasized that the sphere radius plays a significant role in K(t) measurements. [23][24][25] The instantaneous strain ratio corresponding to the spherical indentation test is the ratio of h(t) to the sample thickness [H(t)]. However, the TPE surfaces produce spherical coronal deformation [V g (t)] under external conditions; this results in three-dimensional volumetric changes instead of two-dimensional longitudinal changes.…”
Section: Introductionmentioning
confidence: 99%